Determinants of Nurse Professional Behavior: A cross-Sectional Study of Nurses at Public Health Centers in Indonesia - Dodi Wijaya; Nurfika Asmaningrum; Kholid Rosyidi Muhammad Nur; Murni Herawaty Sitanggang; Yennike Tri Herawati (Babali Nursing Research, 2023)
The provision of health services to the community based on the professional attitudes and behavior of nurses will increase public trust and reduce negative perceptions such as inappropriate actions, lack of skills, lack of communication with patients and lack of speed in responding to patient complaints. The study aimed to determinants that influence the professional behavior of nurses in health centers in Indonesia. An analytic observational study with a cross sectional research design, it was conducted for two months, from August to October 2022. We involved 227 nurses working in 50 puskesmas in Jember Regency, East Java, Indonesia. There are 3 new findings in this study, the following is an explanation of the research findings (1) the professional behavior of nurses is influenced by sociodemographic factors, individual factors, and psychological factors, (2) the determinants that have a major influence on nurses' professional behavior are individual factors, ( 3) Individual factors are reflected by indicators of competence and ability of nurses, (4) The better the competence and ability of nurses, the better the professional behavior of nurses. The professional behavior of nurses is influenced by sociodemographic factors, individual factors, and psychological factors.